5-FU@HFn combined with decitabine induces pyroptosis and enhances antitumor immunotherapy for chronic myeloid leukemia - Zuowei Yuan; Guoyun Jiang; Ying Yuan; Qian Liang; Yaxin Hou; Wenyao Zhang; Lujia Tang; Kelong Fan; Wenli Feng (Journal of Nanobiotechnology)
Abstract Background Tyrosine kinase inhibitors (TKIs) constitute the primary treatment for chronic myeloid leukemia (CML). However, resistance to TKIs often leads to treatment failure. Pyroptosis, a form of programmed cell death, has emerged as a promising strategy in cancer therapy due to its ability to eliminate tumor cells while stimulating antitumor immunity. Low-dose decitabine (DAC) has been shown to reverse methylation-induced silencing of the pyroptosis-related gene gasdermin E (GSDME) in some tumor cells, offering a potential new therapeutic option for CML. Herein, we propose a combination therapy using 5-fluorouracil (5-FU), a broad-spectrum chemotherapeutic agent, and low-dose DAC to induce pyroptosis in CML cells via the caspase-3/GSDME pathway. However, the nonspecific targeting of 5-FU diminishes its pyroptosis efficacy and causes off-target toxicity, highlighting the need for a targeted drug delivery system. Results In this study, we developed 5-FU@HFn nanoparticles (NPs) by loading 5-FU into the recombinant human heavy chain ferritin (HFn) nanocage through a high-temperature via the drug channels on the protein cage. The loading efficiency was approximately 50.62 ± 1.17 µg of 5-FU per mg of HFn. 5-FU@HFn NPs selectively targeted CML cells through CD71-mediated uptake, significantly enhancing the therapeutic effects of 5-FU. When combined with DAC, 5-FU@HFn NPs effectively activated pyroptosis via the caspase-3/GSDME pathway in both TKI-sensitive and TKI-resistant CML cells. In a CML mouse model, this combination therapy significantly suppressed tumorigenesis and triggered a robust antitumor immune response, facilitating the clearance of leukemic cells. Furthermore, the 5-FU@HFn NPs exhibited excellent in vivo safety. Conclusions The innovative therapeutic strategy, combining 5-FU@HFn nanoparticles with low-dose DAC, effectively induces caspase-3/GSDME-mediated pyroptosis and activates antitumor immunity for CML. This approach offers a potential alternative for patients resistant or intolerant to TKIs. Graphical abstract